A deep-sea slant on the molecular phylogeny of the Scleractinia. - Goff-Vitry, L; Rogers, A; Baglow, D (2004)
Lophelia pertusa and Madrepora oculata are azooxanthellate corals with nearly cosmopolitan distributions. They form cold-water reefs in the upper bathyal zone on continental margins and offshore banks [A.D. Rogers, Int. Rev. Hydrobiol. 84 (1999) 315]. Lophelia is classified in the family Caryophylliidae and Madrepora in the family Oculinidae, both on the basis of skeletal morphology. Recent molecular studies of the scleractinians have given a new insight into the evolutionary history of this group. This study was aimed at clarifying the phylogenetic relationships of Lophelia and Madrepora, through the analysis of partial sequences of the mitochondrial 16S rDNA. Sequences were obtained for samples of L. pertusa collected in the northeast Atlantic and off Brazil, M. oculata, four other deep-sea and eight tropical coral species from the Réunion island in the Indian Ocean. The sequences were aligned with 69 homologous sequences of Scleractinia. Maximum parsimony and Bayesian analyses support previously published molecular topologies. The two specimens of L. pertusa grouped with two caryophylliids, confirming the existing classification of the species, but the large genetic distance between the two Lophelia samples suggests that these populations are genetically isolated from one another. M. oculata did not cluster with oculinids, but formed a monotypic clade lying between the families Pocilloporidae and Caryophyliidae. Phylogenetic analysis also suggested cryptic speciation within the tropical taxa Pocillopora meandriana and possibly Acropora humilis.